Income's Role in Mediating Consumption, Education, and Credit Effects on Household Savings - Efriyani Sumastuti; Nuswantoro Setyadi Pradono (Universitas Negeri Semarang, 2025)
This study aims to investigate the mediating role of income in the effects of consumption, education, and credit on household savings among business actors in Indonesia. Using a sample of 170 business owners, data were collected through structured questionnaires covering variables such as monthly consumption, education level, credit usage, income, and household savings. Structural Equation Modeling (SEM) was employed to analyze the data using JASP software, allowing for both direct and indirect effects to be assessed. The results indicate that consumption positively affects both income and household savings, suggesting that increased spending among business actors reflects higher income levels that enable greater saving. Education also positively influences household savings by enhancing financial literacy, though it does not directly increase income. Conversely, higher credit usage is associated with reduced income and household savings, highlighting the financial burden imposed by debt repayment. Income is shown to be a significant mediator in the relationships between consumption, credit, and household savings but does not mediate the effect of education. These findings underscore the importance of financial literacy and responsible credit use in enhancing savings among business actors. The study offers insights for policymakers to promote financial stability and prudent financial behavior